Wzorce wychowania do życia w rodzinie przekazywane dziewczętom w szkołach klasztornych (XVII–XIX w.) - Szylar, Anna (Biuletyn Historii Wychowania, 2013)
Patterns of education for family life for girls in convent schools (XVII – half of XIXth century) The paper aims to analyse the education and upbringing of girls in schools run by nuns in the period from the seventeenth to the mid-nineteenth century. It shows the elements of upbringing and education that shaped the attitudes and values considered the most important in family life. It discusses issues related to the education of girls in how to run and manage a household, how to do household work, how to manage the household expenditure. On the basis of school curricula the range of intellectual education, the development of personal standards (attitudes, behaviours and features of character) of women in this period will be shown. These issues will be presented against a changing historical context, and will focus on girls from different social backgrounds.